2022
DOI: 10.1002/kjm2.12619
|View full text |Cite
|
Sign up to set email alerts
|

CST1 promotes the proliferation and migration of PDGF‐BB‐treated airway smooth muscle cells via the PI3K/AKT signaling pathway

Abstract: Typically, airway remodeling caused by migration and proliferation of airway smooth muscle cells (ASMCs) plays a crucial role in the pathophysiological characteristics of asthma development. Cystatin 1 (CST1), a protein‐coding gene referred to as Cystatin SN, is highly expressed in asthma patients. However, the role of CST1 and related molecular mechanisms in the development of asthma remains to be explored. This study aims to investigate the role of CST1 in asthma progression and present related molecular mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…However, pAKT expression differed between the CM-HTR-8/SVneo shDAB2 group and the CM-HTR-8/SVneo shNC with the CXCR1/2 group, indicating that other cytokines, except CXCL8, activate the PI3K pathway. A study on asthma revealed that activating the PI3K/AKT signaling pathway could promote the migration and proliferation of hVSMC [ 52 ]. Additionally, PDGF-ββ could activate phosphorylation of Akt and induce proliferation and migration of VSMCs [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, pAKT expression differed between the CM-HTR-8/SVneo shDAB2 group and the CM-HTR-8/SVneo shNC with the CXCR1/2 group, indicating that other cytokines, except CXCL8, activate the PI3K pathway. A study on asthma revealed that activating the PI3K/AKT signaling pathway could promote the migration and proliferation of hVSMC [ 52 ]. Additionally, PDGF-ββ could activate phosphorylation of Akt and induce proliferation and migration of VSMCs [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…One study showed that CYS1 promotes the proliferation and migration of airway smooth muscle cells by activating the PI3K/AKT signaling pathway in an in vitro asthma model. This indicates that CYS1 participates in airway remodeling events and maybe a main contributor to asthma development [91].…”
Section: Cystatin Sn (Cys1)mentioning
confidence: 99%